Profiling of Microbiota at the Mouth of Bottles and in Remaining Tea after Drinking Directly from Plastic Bottles of Tea - Anna Wakui; Hiroto Sano; Yuka Hirabuki; Miho Kawachi; Ayaka Aida; Jumpei Washio; Yuki Abiko; Gen Mayanagi; Keiko Yamaki; Kaori Tanaka; Nobuhiro Takahashi; Takuichi Sato (MDPI AG, 2021)
It has been speculated that oral bacteria can be transferred to tea in plastic bottles when it is drunk directly from the bottles, and that the bacteria can then multiply in the bottles. The transfer of oral bacteria to the mouth of bottles and bacterial survival in the remaining tea after drinking directly from bottles were examined immediately after drinking and after storage at 37 °C for 24 h. Twelve healthy subjects (19 to 23 years of age) were asked to drink approximately 50 mL of unsweetened tea from a plastic bottle. The mouths of the bottles were swabbed with sterile cotton, and the swabs and the remaining tea in the bottles were analyzed by anaerobic culture and 16S rRNA gene sequencing. Metagenomic analysis of the 16S rRNA gene was also performed. The mean amounts of bacteria were (1.8 ± 1.7) × 104 colony-forming units (CFU)/mL and (1.4 ± 1.5) × 104 CFU/mL at the mouth of the bottles immediately after and 24 h after drinking, respectively. In contrast, (0.8 ± 1.6) × 104 CFU/mL and (2.5 ± 2.6) × 106 CFU/mL were recovered from the remaining tea immediately after and 24 h after drinking, respectively. Streptococcus (59.9%) were predominant at the mouth of the bottles immediately after drinking, followed by Schaalia (5.5%), Gemella (5.5%), Actinomyces (4.9%), Cutibacterium (4.9%), and Veillonella (3.6%); the culture and metagenomic analyses showed similar findings for the major species of detected bacteria, including Streptococcus (59.9%, and 10.711%), Neisseria (1.6%, and 24.245%), Haemophilus (0.6%, and 15.658%), Gemella (5.5%, and 0.381%), Cutibacterium (4.9%, and 0.041%), Rothia (2.6%, and 4.170%), Veillonella (3.6%, and 1.130%), Actinomyces (4.9%, and 0.406%), Prevotella (1.6%, and 0.442%), Fusobacterium (1.0%, and 0.461%), Capnocytophaga (0.3%, and 0.028%), and Porphyromonas (1.0%, and 0.060%), respectively. Furthermore, Streptococcus were the most commonly detected bacteria 24 h after drinking. These findings demonstrated that oral bacteria were present at the mouth of the bottles and in the remaining tea after drinking.